Mechanism of interaction of aluminium with polysilicon when forming an ohmic contact by methods long and rapid heat treatments - Pilipenka, Uladzimir A.; Kovalchuk, Natalia S.; Zhyhulin, Dmitry V.; Shestovski, Dmitry V.; Anishchik, Viktor M.; Ponariadov, Vladimir V. (Journal of the Belarusian State University. Physics, 2024)
It has been established that the formation of ohmic contact between aluminium and polysilicon occurs due to the mutual diffusion of aluminium into polysilicon and silicon into aluminium. It is shown that their diffusion mainly occurs through the intergranular space in both the polysilicon film and the aluminium film. The diffusion coefficients of aluminium in polysilicon and silicon in aluminium were determined at a heat treatment temperature of 450 °C, used in the creating of semiconductor devices and integrated circuits. It is noted that diffusion processes obey the Kirkendall effect, leading to a displacement of the aluminium – polysilicon interface to the surface of the silicon dioxide film until the complete dissolution of polysilicon in aluminium. The formation of polysilicon conglomerates occurs when the aluminium film cools due to the release of silicon from it onto the surface of the SiO2 film. The precipitation of silicon begins at the locations of triple points (the junction of three grains) in the structure of the aluminium film, since due to their large intergranular space, the mobility of silicon atoms in them is maximum. Subsequently, these places become centers of silicon segregation, which leads to the formation of polysilicon conglomerates in the aluminium film. In contrast to long heat treatment, the use of rapid heat treatment does not lead to the formation of such conglomerates, and diffusion processes little change the aluminium – polysilicon interface due to the short time of exposure to temperature.